Effect of genotype on the disease course in idiopathic pulmonary fibrosis despite antifibrotic treatment - Sterclova, Martina; Kishore, Amit; Sikorova, Katerina; Skibova, Jelena; Petrek, Martin; Vasakova, Martina (Biomedical reports, 2021)
A genetic predisposition has been identified in 30% of idiopathic pulmonary fibrosis (IPF) cases. Although it is highly probable that the genotype affects the disease susceptibility and course in almost all patients, the specific genotype goes undetected. The aim of the present study was to explore the effects of variants of the genes encoding interleukin-4 (IL-4), mucin 5B (MUC5B), toll interacting protein (TOLLIP), surfactant protein A (SFPTA), transforming growth factor-β (TGF-β) and transporters associated with antigen processing (TAP1 and TAP2) on the course of IPF. A total of 50 patients with IPF were enrolled, and variants of these genes were assessed. Lung function at the time of diagnosis and after 6, 12 and 18 months, and the number of acute exacerbations and deaths in each observation period were measured. ANOVA was used to test the association between gene polymorphisms and the decrease in lung function. There was no significant effect of the gene polymorphisms on the outcomes of patients up to 6 months during the observation period. After 12 months, an effect of an IL-4 single nucleotide polymorphism (SNP) (rs 2070874) on patient outcomes was observed [relative risk (RR) for T allele: 5.6; 95% confidence interval (CI), 0.79-39.0; P=0.053]. The RR of progression in patients with the IL-4 SNP (rs 2243250) and the CT and TT genotypes was 4.3 (95% CI, 1.1-17.5; P=0.046). A total of 18 months after the diagnosis of IPF, an effect of the TOLLIP polymorphism on patient outcome was detected (rs 111521887; risk allele GC; RR: 7.2; 95% CI, 0.97-53.6; P=0.052). Thus, IL-4 and TOLLIP gene polymorphisms may represent disease course-modifying factors, but not drivers of IPF.
Keywords: toll interacting protein; gene variants; idiopathic pulmonary fibrosis; interleukin 4